ERECTOR SPINAE PLANE BLOCK - Silva, Wallace Andrino; de Sousa Arruda, Isis Caroline (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2020)
The erector spinae plane block is an interphase analgesic block initially described for the treatment of acute and chronic neuropathic pain of the chest wall. Since the initial description in 2016, several applications and modifications to the original technique have been published. It consists of a block of easy accomplishment, wide area of ??analgesia and low rate of complications, which gives it an advantage over other chest wall blocks. The mechanism of action, the dispersion pathway and the effective doses of local anesthetics, however, are still not entirely understood. Key words: pain; anesthesia; erector spinae plane block;